2021
DOI: 10.1155/2021/6621507
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein E46K Mutation and Involvement of Oxidative Stress in a Drosophila Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is an age-associated neurodegenerative condition in which some genetic variants are known to increase disease susceptibility on interaction with environmental factors inducing oxidative stress. Different mutations in the SNCA gene are reported as the major genetic contributors to PD. E46K mutation pathogenicity has not been investigated as intensive as other SNCA gene mutations including A30P and A53T. In this study, based on the GAL4-UAS binary genetic tool, transgenic Drosophila mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Studies have shown that the herbicide paraquat has neurotoxic effects ( Chaudhuri et al, 2007 ) and Drosophila models exposed to PQ are often used as the models of neurodegenerative diseases to find new neuroprotective compounds ( Jaiswal et al, 2012 ; Fernández-Hernández et al, 2016 ; Hajji et al, 2019 ). Here, Drosophila were treated with 6 mg/ml Paraquat dichloride (methyl viologen; PQ) in a sucrose solution, which provides basic energy for survival, for 24 h ( Reiszadeh Jahromi et al, 2021 ). The data showed that 6 mg/ml PQ exposure led to lethal effects in Drosophila , and the survival rate was 50%.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the herbicide paraquat has neurotoxic effects ( Chaudhuri et al, 2007 ) and Drosophila models exposed to PQ are often used as the models of neurodegenerative diseases to find new neuroprotective compounds ( Jaiswal et al, 2012 ; Fernández-Hernández et al, 2016 ; Hajji et al, 2019 ). Here, Drosophila were treated with 6 mg/ml Paraquat dichloride (methyl viologen; PQ) in a sucrose solution, which provides basic energy for survival, for 24 h ( Reiszadeh Jahromi et al, 2021 ). The data showed that 6 mg/ml PQ exposure led to lethal effects in Drosophila , and the survival rate was 50%.…”
Section: Resultsmentioning
confidence: 99%
“…PQ exposure was used in Drosophila to study PD [ 20 , 34 , 35 , 36 , 38 ]. However, the acute dose of PQ used in these models (10 or 20 mM fed to adult flies, depending on the studies) led to rapid loss of fly viability within 2–3 days, which precluded a fine analysis of the effect of PQ on αSyn protein.…”
Section: Resultsmentioning
confidence: 99%
“…PQ exposure is also commonly used to study PD in Drosophila that do not overexpress human SNCA gene [ 20 , 34 , 35 , 36 ]. In this model, fly mortality was used as proxy of PQ toxicity to identify the mechanism regulating the stress response to PQ [ 15 , 37 , 38 ]. In some studies, but not all, PQ acute exposure was also associated with the loss of dopaminergic neurons [ 37 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, elevated 3-nitrotyrosine and nitrated alpha-synuclein immunoreactivity have been found in Parkinson’s disease patients’ Lewy bodies [ 36 ]. Intracellular peroxynitrite generation causes Alpha--synuclein aggregation [ 37 ], and oxidative damage inhibits ubiquitination and proteasome-mediated protein degradation [ 38 ]. These results demonstrate a probable relationship between oxidative damage and the production of protein aggregates that are hallmarks of Parkinson’s disease.…”
Section: Pathogenesis Of Parkinson’s Diseasementioning
confidence: 99%